2007
DOI: 10.3766/jaaa.18.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of an Asymmetric Directional Microphone Fitting

Abstract: Laboratory evidence suggests that an asymmetric microphone fitting (omnidirectional processing in one ear and directional processing in the other) can provide a directional advantage in background noise that is as great, or nearly as great, as that provided by binaural directional processing (Bentler et al, 2004). The present study investigated whether the potential benefit of an asymmetric fitting observed in the laboratory extends to real-life listening. Specifically, ease of listening was compared across a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…EMA has been implemented using “low-tech” paper-and-pencil journals in previous hearing aid outcome research (Preminger and Cunningham, 2003; Walden et al, 2004; Cord et al, 2007; Wu and Bentler, 2010b, 2012). For example, to compare two hearing aid gain settings, Preminger and Cunningham (2003) asked participants to report the degree of listening difficulty and sound clarity of hearing aids in journals three times each day.…”
Section: Introductionmentioning
confidence: 99%
“…EMA has been implemented using “low-tech” paper-and-pencil journals in previous hearing aid outcome research (Preminger and Cunningham, 2003; Walden et al, 2004; Cord et al, 2007; Wu and Bentler, 2010b, 2012). For example, to compare two hearing aid gain settings, Preminger and Cunningham (2003) asked participants to report the degree of listening difficulty and sound clarity of hearing aids in journals three times each day.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested that, in elderly individuals with complaints of difficulty in understanding speech in noise, noise reduction is used as the default setting of programming. However, regarding the directional microphone, in order to find more than satisfactory results and, in this research, it has been shown as essential when the source of the noise came from behind the individual, their adjusted activation is not recommended as it may interfere in speech understanding in quiet environments and lower awareness of environmental sounds (29) . Thus, it is advised to combine directional and omnidirectional microphones.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is advised to combine directional and omnidirectional microphones. A possible combination would be to adjust one ear with directional microphone and the other with omnidirectional microphone, which has proven performance in speech understanding, close to or comparable to performance with the use of directional microphones in both hearing aids (21,29) . Other options would be the directional microphone added to another program, or even the use of adaptive directional microphone, which switches automatically between omnidirectional or directional microphone, if the noise is detected.…”
Section: Discussionmentioning
confidence: 99%
“…In monaurally HI persons, who have hearing loss in only one ear, the ear with normal hearing can be used for the detection of such informative ambient sounds; however, in binaurally HI persons who use independently operated, forward‐focusing HS devices in both ears, most ambient sounds not in front of the person may be attenuated. Therefore, in order to provide a more natural ambient sound to binaurally HI persons without increasing the interference of ambient noises, several groups have suggested the concept of an asymmetric directional microphone (DM) algorithm, which applies the forward‐focusing beamformer to one ear and an omnidirectional microphone (OM) algorithm to the other ear simultaneously . However, in most conventional bilateral asymmetric DM algorithms, two HS devices are operated independently, and therefore, several limitations exist: (i) the direction of the most dominant noise source (DN) around the listener cannot be determined because comparison between the two devices is not available; and (ii) when the DN moves near the OM‐mode device, the roles of the DM‐mode and OM‐mode devices cannot be switched automatically to minimize the interference of the DN.…”
mentioning
confidence: 99%